PENGARUH PENGGUNAAN SUKROSA DAN IBA TERHADAP INDUKSI AKAR EKSPLAN TUNAS ANGGREK (Dendrobium sp.) SECARA IN VITRO - Nurmila Karimah; Florentina Kusmiyati; Syaiful Anwar (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2021)
Dendrobium sp. is well known as the largest genus in orchid, every region has its own characteristics. The aim of the research was to examine the interaction effect of sucrose and IBA (indole 3-butyric acid) on root initiation of Dendrobium sp. in vitro culture. This study used a completely randomized design (CRD) factorial design 3x4 with 3 replications. The first factor was sucrose concentration (S) : S1 (20 g/l), S2 (30 g/l) and S3 (40 g/l). The second factor was IBA concentration (I) : I0 (0 mg/l), I1 (1 mg/l), I2 (2 mg/l) and I3 (3 mg/l). The parameters observed were number of roots, length of root, initiation root period, height of plantlets, number of shoots and culture success percentages. Data was analysed using analysis of variance and further test using LSD (least significance different) with a 5% level. The result showed that the concentration of sucrose 40 g/l had a significant effect on number of roots, length of root, height of plantlets and number of shoots. Concentrations of IBA 2 mg/l had a significant effect on height of plantlets. Iinteraction of both sucrose and IBA had no significant effect on all of the parameters. Two objects of culture were contaminated by fungi. Suggest for this study was to increase sucrose and IBA concentrations for the best result combination